Man in the cinema house - Mercado, Bernard Jay 1994-; Mercado, Bernard Jay (2015)
"A Ma is imprisoned in a movie theater for killing Jose Rizal. He attempts to escape. Man in the Cinema House is a tempo-spatial critique on the cinematic institution, its conventions and exploitation that have been normalized. It is a love letter to cinema, but at the same time, a protest to the very institution that guides its creation. The Man is the ghost of cinema as much as the spectator becomes a "ghost" when watching a film in the movie theater. The film challenges the boundaries of cinema both in the metaphorical sense and the meta-physical method. The angry movie Man escapes, declaring that he is no more a ghost, but free of the restrictions of cinema. He recognizes that he has become a Self."